Comparison of Physicochemical Properties, Fatty Acid Composition and Mineral Contents in Common Carp (Cyprinus carpio L.) Fillet and the Native Traditional Product Carp Ham - Skałecki Piotr (Polish Journal of Food and Nutrition Sciences, 2016)
Based on the analysis of the proximate composition, mineral contents and fatty acid profiles, the objective of this study was to evaluate the nutritional value of the traditional product Carp Ham produced from common carp raw fillets. Significant differences were found in the proximate composition and mineral contents between the raw fillets and the final product. The contents of protein, fat and ash in 100 g of the traditional product (21.94, 8.63 and 6.58 g) were higher (P<0.01) than in fillets (19.28, 1.53 and 1.22 g), with an exception of the moisture content (63.60 vs. 77.79 g). Significantly higher energetic value showed Carp Ham (692 kJ/100 g) as compared to fillets (384 kJ/100 g). Carp fillet and Ham showed high values of the index of nutritive quality (INQ) for protein (8.43 and 5.44). Processing had a significant influence (P<0.05) on the decrease of K, Mg and Ca contents in Carp Ham (3107.8, 236.2 and 107.7 mg/kg), and the increase of Fe, Zn, Mn and Cu concentrations (2.10, 3.10, 0.50 and 0.16 mg/kg). Among the fatty acids, the only significant differences were stated for C20:1n-9 (2.22 vs. 1.76%) and C22:6n-3 (1.34 vs. 0.83%), with the higher values determined for fillets. The traditional product, Carp Ham, preserved positive nutritional features, which were better highlighted by the fatty acid composition, health-related indices and oxidative stability. The study indicated that the traditional manufacturing method retains the most part of the nutritional constituents present in the carp fillets.